ADVANTAGES AND DISADVANTAGES OF BUILDING THE NETWORK ON THE BASE OF GPON TECHNOLOGY - Khusanova, S.Sh.; Makhmudov, I.A.; Komilov, D.R. (Educational Research in Universal Sciences, 2023)
Services such as IP television (IPTV) and watching and downloading high-quality videos over the Internet require high network bandwidth from the Internet channel. ADSL and XDSL technologies have some limitations on cable length and channel bandwidth.